2008
DOI: 10.1021/jm800608s
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Positron Emission Tomography (PET) Imaging with an αvβ6 Specific Peptide Radiolabeled using 18F-“Click” Chemistry: Evaluation and Comparison with the Corresponding 4-[18F]Fluorobenzoyl- and 2-[18F]Fluoropropionyl-Peptides

Abstract: Numerous radiolabeled peptides have been utilized for in vivo imaging of a variety of cell-surface receptors. For applications in PET using [ 18 F]fluorine, peptides are radiolabeled via a prosthetic group approach. We previously developed solution-phase 18 F-"click" radiolabeling and solid-phase radiolabeling using 4-[ 18 F]fluorobenzoic and 2-[ 18 F]fluoropropionic acids. Here we compare the 3 different radiolabeling approaches and report the effects on PET imaging and pharmacokinetics. The prosthetic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 35 publications
2
70
0
Order By: Relevance
“…It has previously been demonstrated that the addition of bulky chelators or prosthetic groups can affect the binding, internalization, and metabolism of receptor targeting peptides [2528]. The in vitro cell binding and internalization assays revealed that all four radiotracers show binding directed towards the integrin α v β 6 with fairly comparable internalization levels, indicating that the addition of a chelator and the radiolabeling with 64 Cu did not drastically affect the binding potential of the PEG 28 -A20FMDV2 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that the addition of bulky chelators or prosthetic groups can affect the binding, internalization, and metabolism of receptor targeting peptides [2528]. The in vitro cell binding and internalization assays revealed that all four radiotracers show binding directed towards the integrin α v β 6 with fairly comparable internalization levels, indicating that the addition of a chelator and the radiolabeling with 64 Cu did not drastically affect the binding potential of the PEG 28 -A20FMDV2 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Additionally, fluoride capturing reactions based on peptide modifications allow for stable peptide-Si- 18 F, peptide-B- 18 F, and peptide-chelator-Al- 18 F bonds to be generated rapidly and efficiently. [23,3338] Collectively, these studies indicate a correlation between the prosthetic group and the biodistribution of the radiotracer, [39,40] highlighting the importance of the ability to test different prosthetic groups on a radiolabeled peptide.…”
mentioning
confidence: 99%
“…For the present study, solid-phase peptide synthesis and radiolabeling of the 18 F and 64 Cu tracers followed robust protocols, 15,21,25 yielding the radiotracers in high radiochemical purity (≥ 99%).…”
Section: Discussionmentioning
confidence: 99%